Disfunciones visomotoras y visoperceptuales en niños con diagnóstico de TDAH en una institución educativa (2020)
There is little information from studies in Colombia and specifically in the city of Medellín evaluating the visual-perceptual abilities of school children diagnosed with attention deficit hyperactivity disorder syndrome (ADHD) because this disorder is managed by different specialties. Bibliographic references When consulted, they sometimes offer opposite management, which is why the importance of this project will provide us with new data that basically focuses on the visual and perceptual part. Our interest has been based on the impact that visual and/or perceptual disturbances can have on the development of ADHD